Indoor hygrothermal condition and user satisfaction in naturally ventilated historic houses in temperate humid continental climate around the Baltic Sea. (2nd January 2016) - Alev, Üllar; Kalamees, Targo; Eskola, Lari; Arumägi, Endrik; Jokisalo, Juha; Donarelli, Anna; Siren, Kai; Broström, Tor
Abstract : Indoor climate and user satisfaction were analysed by field measurement and a questionnaire in 67 traditional rural houses in Estonia, Finland and Sweden. Our findings showed that the indoor climate in all the investigated historic rural houses needs improvement. The room temperature was mainly too low during winter. Leaky houses had also a larger vertical temperature difference. The relative humidity in the unheated and periodically heated houses was high during winter and caused risk for mould growth in 17% of all houses and 33% of unheated houses. Significant differences of indoor humidity loads in different houses were revealed depending on the living density and usage profile. During the winter period, the design value of moisture excess was 4–5 g/m 3 and the average moisture load was 2–3.5 g/m 3 . The indoor humidity load in historic houses was similar to that in modern houses. The results of the questionnaire showed that main problems were related to unstable or too low temperatures. At the same time, inhabitants rated the overall indoor climate as healthy and no statistically important relations were found between average indoor temperature and complaints about too cold or too warm indoor temperatures.